TEEMO: Trusted peripheral monitoring for optical networks and beyond - Busch, Marcel; Schlenk, Ralph; Heckel, Hans (Proceedings of the 4th Workshop on System Software for Trusted Execution, SysTEX 2019, 2019)
Recent trends like edge computing move metro and core network elements from access restricted back offices to data centers where their attack surface is exposed to a larger audience. These trends increase the need for means of monitoring these network elements’ peripherals in a secure and untampered way. In this paper we introduce the use case of trusted peripheral monitoring on optical network elements. For network operators it is important to keep an untampered log of their network’s configuration. But the effective settings can only be retrieved from a network element’s hardware itself requiring the retrieval process to be trusted. We propose TEEMo, an infrastructure for trusted peripheral monitoring for embedded devices based on ARM TrustZone. TEEMo establishes a trusted path between peripheral configuration lookup and reporting to a remote log server and reports the current configuration on an interval basis. We present a case study of porting TEEMo to an existing commercial networking product and share our experiences. Finally, we evaluate the performance of the solution and discuss the additional security.
CRIS-Team Scopus Importer:2019-12-31
Keywords: ARM trustzone; Peripheral monitoring; Trusted computing